Diversity of leaf rust resistance in Indonesian sorghum genetic resources - FAWWAZ DINANTY; DESTA WIRNAS; TRIKOESOEMANINGTYAS TRIKOESOEMANINGTYAS; ABDJAD ASIH NAWANGSIH (Society for Indonesian Biodiversity, 2022)
Abstract. Dinanty F, Wirnas D, Trikoesoemaningtyas, Nawangsih AA. 2022. Diversity of leaf rust resistance in Indonesian sorghum genetic resources. Biodiversitas 23: 2570-2579. Sorghum is an alternative source as a substitute for rice. Leaf rust (Puccinia purpurea) is a constraint in sorghum cultivation and resistance to rust disease is a condition for releasing sorghum varieties. This study aimed to screen sorghum accessions for resistance to leaf rust disease. The screening was carried out on 48 sorghum accessions and seven check varieties, namely Numbu, Kawali, Bioguma 1, Pahat, Soraya 1, Soraya 2, and Soraya 3. Evaluation of leaf rust resistance under field conditions was carried out in IPB University experimental field Cikarawang-Bogor (275 asl) from February 2021 to June 2021. The experiment was conducted in an augmented design with four replications for check varieties. Identification of leaf rust resistance was also carried out using molecular markers designed from the Lr34 and Rp1D genes. The results revealed that 5 genotypes, namely genotypes 31 (Demak 2), 24 (IS 18551), 43 (Lokal bima 3), 17 (ICSV 93036), and 33 (Demak 5) were resistant to leaf rust with high yield potential. The results of identification using molecular markers showed that all accessions had Lr34 and Rp1D gene fragments.